"To your petit-bourgeois feminism, I prefer the real one" : discursive constructions of identities and ideologies in feminism-centred plenary debates in the European Parliament - Aracil, Ainhoa de León (2021)
Political communication in the 21st century is largely centred on the concepts of identity and ideology. Considerable research has explored either identity construction or ideology in the context of parliamentary political communication, but little research has examined the interrelation of identification processes and the negotiation of ideologies. Further, only a small percentage of research in this context has observed identity as constructed in communication, ideology as discursively constructed or worked in an international setting. The present study addresses these gaps by discursively analysing the processes of constructing and negotiating the meanings of identities and ideologies in the context of women-centred plenary debates in the European Parliament. The aim of this study is to explore how identities and ideologies are constructed and negotiated in front-stage political communication. Owing to the increased influence of political communication in the social sphere, particularly when referring to groups traditionally excluded from power, the study analyses debates where the figure of the woman is central. This study analyses 6 women-centred debates from 5 plenary sessions, which are temporally distributed between January 1st and March 31st of 2020. The analysis was conducted using concepts of Critical Discursive Psychology, which observes identity categories as produced communicatively and informed by the speaker‘s available beliefs, as a methodological tool, and intersectional feminism as a framework. Results show that speakers in the European Parliament make use of seven discursive strategies to construct and negotiate the meanings of identities and ideologies. Additionally, results show that these discursive constructions, which have major effects at a legislative and social level for their power to orient action, are influenced by context, power-relations, the backstage of politics and situated political goals.